Oral hygiene education of special needs children. Part 2: visually impaired children. Issue 1 (1st January 2019) - Doichinova, Lilia; Gateva, Natalia; Hristov, Krasimir
Abstract: The purpose of this study was to implement an educational programme for oral hygiene for visually impaired children. It involved 30 children with total blindness aged 7–14 years: 13 boys and 17 girls. For their training, specially designed training materials were made, including magnified gypsum teeth models with and without cavities resembling carious lesions, Braille instructions for oral hygiene and embossed images printed out on special microcapsule paper presenting the sequence of the toothbrushing movements. To facilitate the maintenance of oral hygiene at home, a special CD with children's favourite music was made, divided into fragments by a bell ring that indicates the time to change the area to be toothbrushed. The music meets the time required to clean all the tooth surfaces for three minutes. The oral hygiene level was assessed using the Greene and Vermillion – Simplified Oral Hygiene Index. The approved one-year oral hygiene educational programme showed a significant improvement in the oral hygiene habits of the visually impaired children. There was a slow improvement in the oral hygiene levels in the first month. The trend continued until the end of the one-year period, the results obtained being statistically significant compared to the baseline. The motivation and education of visually impaired children with Braille instructions and magnified tooth models were essential to improve the oral hygiene status.